PROGRAM PERILAKU HIDUP BERSIH DAN SEHAT (PHBS): STUD! KASUS DI KABUPATEN BANTUL 2003 = CLEAN AND HEALTHY LIFE BEHAVIOUR (CHLB) PROGRAM:... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Background: Clean and Healthy Life Behavior (CHLB), as part of social movement strategies initiated by the Ministry of Health, has been implemented in the Bantul District of Yogyakarta since 1996. The movement is organized through existing puskesmas in the area. Various level of participation has been noted among the areas of implementation. One area of Puskesmas Kasihan 2 has been known as one the success story of the CHBL implementation. The main aim of this study is to explore and to learn the major factors that contribute to this success story. Data and Method: This is a case study that treats community as our main unit of analysis. Two puskesmas areas: Kasihan 2 and Banguntapan 1 were selected as our study focus. The data were collected from JulyâSeptember 2004 through in depth interviews of the community leaders and health staffs from public health centers and district health office. Two focused group discussions were also done. Findings: What we can learn from this case is that earlier experience between community and government helps the development and the work of the Clean and Healthy Life Behavior Program in the Kasihan 2 Puskesmas Area. In addition to this, the presence of nor or two community leaders who have the background of working together with the community is the key to the success of health social movement. We also learn that government initiatives and acting as a sparing partner to the community allow community show their performance in the health game. Heath cadres have no longer become the object. They play their role as the government officers play their own. We believe that puskesmas managers should have the capability to identify community leaders in their working areas to invite them to work together in a game. The philosophy of partnership and supporting their staff in working together with the community could become the puskesmas agenda. Keywords: Clean and Healthy Life Behavior, community leadership, government initiative, partnership between government and community